Atmospheric CO2 mole fraction affects stand‐scale carbon use efficiency of sunflower by stimulating respiration in light. (1st February 2017) - Gong, Xiao Ying; Schäufele, Rudi; Lehmeier, Christoph Andreas; Tcherkez, Guillaume; Schnyder, Hans
Abstract: Plant carbon‐use‐efficiency (CUE), a key parameter in carbon cycle and plant growth models, quantifies the fraction of fixed carbon that is converted into net primary production rather than respired. CUE has not been directly measured, partly because of the difficulty of measuring respiration in light. Here, we explore if CUE is affected by atmospheric CO2 . Sunflower stands were grown at low (200  μ mol mol −1 ) or high CO2 (1000  μ mol mol −1 ) in controlled environment mesocosms. CUE of stands was measured by dynamic stand‐scale 13 C labelling and partitioning of photosynthesis and respiration. At the same plant age, growth at high CO2 (compared with low CO2 ) led to 91% higher rates of apparent photosynthesis, 97% higher respiration in the dark, yet 143% higher respiration in light. Thus, CUE was significantly lower at high (0.65) than at low CO2 (0.71). Compartmental analysis of isotopic tracer kinetics demonstrated a greater commitment of carbon reserves in stand‐scale respiratory metabolism at high CO2 . Two main processes contributed to the reduction of CUE at high CO2 : a reduced inhibition of leaf respiration by light and a diminished leaf mass ratio. This work highlights the relevance of measuring respiration in light and assessment of the CUE response to environment conditions. Abstract : Understanding the response of plant carbon use efficiency (CUE = NPP/GPP) to atmospheric CO2 is important for estimating terrestrial primary production and carbon–climate feedbacks. This study provides CUE data that integrate measured respiration in light and assess the CO2 effect on the properties of the substrate supply system of respiration. The observed lower CUE of sunflower at high CO2 was mostly caused by a respiratory effect. The findings provide an explanation for the phenomenon that plant biomass production has increased to a lesser degree than rates of photosynthesis under elevated CO2 . The main highlights of the new paper are the following: This study provides the first experimental evidence that high atmospheric CO2 reduces the inhibition of stand‐scale respiration in light and hence diminishes carbon use efficiency (CUE = NPP/GPP). This is the first study examining the effect of atmospheric CO2 concentration on the kinetic properties of the substrate pool system that supplies whole‐plant respiration. The manuscript provides the theoretical framework that underlies a novel 13 C labelling approach for (i) partitioning of apparent photosynthesis and respiration in light and (ii) compartmental modelling of the substrate supply system of respiration.